2007
DOI: 10.1086/522986
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis after Initiation of Antiretroviral Therapy in Low-Income and High-Income Countries

Abstract: We examined the incidence of and risk factors for tuberculosis during the first year of highly active antiretroviral therapy in low-income (4540 patients) and high-income (22,217 patients) countries. Although incidence was much higher in low-income countries, the reduction in the incidence of tuberculosis associated with highly active antiretroviral therapy was similar: the rate ratio for months 7-12 versus months 1-3 was 0.48 (95% confidence interval, 0.36-0.64) in low-income countries and 0.36 (95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 10 publications
(6 reference statements)
5
26
1
Order By: Relevance
“…However, TB incidence may rise during the initial months on ART, which is largely due to ART-induced unmasking of subclinical active TB and delayed diagnosed of unspecific symptomatic patients in resource-limited settings[1315]. The TB incidence pattern following ART initiation in the current study is consistent with findings from previous studies[1620]. Data from South Africa[18, 20] and Nigeria[19] both demonstrated that TB incidence was higher in the first year of ART, then decreased over time thereafter.…”
Section: Discussionsupporting
confidence: 88%
“…However, TB incidence may rise during the initial months on ART, which is largely due to ART-induced unmasking of subclinical active TB and delayed diagnosed of unspecific symptomatic patients in resource-limited settings[1315]. The TB incidence pattern following ART initiation in the current study is consistent with findings from previous studies[1620]. Data from South Africa[18, 20] and Nigeria[19] both demonstrated that TB incidence was higher in the first year of ART, then decreased over time thereafter.…”
Section: Discussionsupporting
confidence: 88%
“…Up to 70% of patients with TB in sub-Saharan Africa are HIV-infected, and TB incidence rates following ART initiation are high, particularly among those with advanced HIV disease 4, 5 . Autopsy studies from sub-Saharan Africa, South East Asia and the Americas confirm TB as the primary or contributing cause of mortality in the majority of cases with nearly half of the TB undiagnosed pre-mortem 6 .…”
Section: Introductionmentioning
confidence: 99%
“…TB incidence rates are very high during the initial months of ART and decrease with increasing duration of treatment [23, 24, 42-44] (Figure 5). Although overall rates are much higher in resource-limited settings, the proportionate reduction in rates during ART is similar in high- and low-income settings [44].…”
Section: Introductionmentioning
confidence: 99%
“…Although overall rates are much higher in resource-limited settings, the proportionate reduction in rates during ART is similar in high- and low-income settings [44]. In a South African study, TB risk was strongly associated with changes in CD4 cell counts measured serially during ART [12**].…”
Section: Introductionmentioning
confidence: 99%